A Pathway to Natural Cancer Therapy; Exploring Zerumbone’s Multitargeted Anticancer Actions - Aloqbi, Akram Ahmed (International Journal of Pharmaceutical Investigation, 2025)
Background A compound called zerumbone found in gingers rhizome has demonstrated potential in fighting cancer due to its beneficial effects on the body. This thorough examination delves into how zerumbone works to combat cancer by triggering cell death through pathways and controlling cell division while influencing signaling routes, like EGFR and VEGFR as well as NF kappa B. Materials and Methods Zerumbone also shows anti-inflammatory characteristics by decreasing inflammation related proteins and oxidative damage and hampers the formation of blood vessels and spread of cancer cells by focusing on factors such as VEGFR and MMP enzymes along with the transition, between different cell types. Results Moreover, zerumbone shows promise, in tackling drug resistance by reducing the activity of Multidrug Resistance (MDR) proteins and focusing on cancer stem cells which makes it a hopeful addition to chemotherapy. Nevertheless, obstacles like bioavailability, formulation stability issues and insufficient clinical data still hinder its use in therapy. Conclusion More research is needed to tackle these challenges and validate the effectiveness and safety of zerumbone paving the path for its integration, into cancer treatment approaches.
Keywords: Anticancer; Apoptosis; Caspases; Ginger; Targeted therapy; Tumor